Numerical solution of binary chemical reaction on stagnation point flow of Casson fluid over a stretching/shrinking sheet with thermal radiation. (15th January 2016) - Abbas, Z.; Sheikh, M.; Motsa, S.S.
Abstract: This study presents the heat and mass transfer analysis in an unsteady boundary layer flow of a Casson fluid near a stagnation point over a stretching/shrinking sheet in the presence of thermal radiation. For thermal radiation, we consider the linear Rosseland approximation. The effects of binary chemical reaction with Arrhenius activation energy are also considered by taking chemical reaction rate as the function of temperature. The numerical solutions of the system of nonlinear PDEs valid for all times in the whole domain (0 ≤  η  ≤ ∞) are obtained by using bivariate spectral collocation quasi-linearization method. The numerical results are then discussed graphically in the form of velocity, temperature and concentration fields for several physical parameters of interest. Hightlights: Study of binary chemical reaction and activation energy with thermal radiation. The developed model of a non-Newtonian fluid in boundary layer flow with diffusivity for concentration of species. Numerical simulation is developed for solution of nonlinear partial differential equations.